Clinical aspects and outcome measures in patients classified as possible sepsis in the emergency department of a brazilian tertiary hospital (Research, Society and Development, 2023)
Objective: To describe the clinical characteristics and outcome of patients classified as possible sepsis in the emergency department of a Brazilian tertiary hospital. Method: retrospective study, involving patients admitted to an emergency service with secondary data and including 468 patients classified with the discriminator “Possible Sepsis” in the year 2018. The analysis was performed using descriptive statistics. The comparison of the outcome with the demographic profile, clinical profile, organic disfunctions and management protocol was carried out by applying Pearson's chi-square test. Results: There were 316 hospitalizations of patients classified through the Manchester Risk Classification System as possible sepsis. Of these, 11.1% were transferred to the intensive care unit, 56.4% to the hospitalization unit and 3% died in the emergency department. The initial suspicion of sepsis raised by the possible sepsis discriminator of the Manchester Risk Classification System was very sensitive and determined the early initiation of initial sepsis management measures. In the analyzed patients, 16% were at high risk for developing organ dysfunction (qSOFA> 2). In addition, we found some difficulties for professionals in implementing Bundle interventions in the first hour in sepsis care. Conclusion: The need for early recognition, but also for the treatment of sepsis as a priority in health services, is evident. Tools such as qSOFA can be associated in screening with protocols already performed, qualifying the early identification and treatment of sepsis.